Revisiting the Emergence of the Modern Business Enterprise: Entrepreneurship and the Singer Global Distribution System - Casson, Mark; Godley, Andrew (Journal of Management Studies, 2007)
This paper approaches the question of why entrepreneurial firms exist from a broad business historical perspective. It observes that the original development of the modern business enterprise was very strongly associated with entrepreneurial innovation rather than an extension of managerial routine. The widely-used theory of the entrepreneur as a specialist in judgmental decision making is applied to the particular point in time when entrepreneurs had to develop novel organizational designs in what Chandler described as the prelude to the 'managerial revolution'. The paper illustrates how the theory of entrepreneurship then best explains the rise of the modern corporation by focusing on the case study of vertical integration "par excellence", Singer. Copyright Blackwell Publishing Ltd 2007.
Keywords: Teaching Business History